Giving full measure to countermeasures : addressing problems in the DoD program to develop medical countermeasures against biological warfare agents - Joellenbeck, Lois M. (Lois Mary), 1963-; Durch, Jane; Benet, Leslie Z. (Online access: NCBI NCBI Bookshelf., 2004)
"In recent years, substantial efforts have been initiated to develop new drugs, vaccines, and other medical interventions against biological agents that could be used in bioterrorist attacks against civilian populations. According to a new congressionally mandated report from the Institute of Medicine and National Research Council of the National Academies, to successfully develop these drugs, vaccines, and other medical interventions against biowarfare agents, Congress should authorize the creation of a new agency within the Office of the Secretary of the U.S. Department of Defense. The committee recommended that Congress should improve liability protections for those who develop and manufacture these products, to stimulate willingness to invest in new research and development for biowarfare protection. Giving Full Measure to Countermeasures also identifies other challenges such as the need for appropriate animal models and laboratories equipped with high-level biosafety protections that will require attention if DoD efforts to develop new medical countermeasures are to be successful."--Publisher's description